Dor lombar crônica: análise dos afastamentos do trabalho e eficácia de tratamento com terapia de fotobiomodulação - Pimenta, Layana de Souza Guimarães (2020)
Low back pain is the main cause of disability worldwide and it is an important public health problem due to its high prevalence. The cost related to low back pain is high, as it is associated with the frequent use of health services and a high rate of absence from work in young adults. Costs are divided into costs of healthcare and production loss. Costs for production loss are generally related to absenteeism and account for the largest share of costs, accounting for about 90% of total costs. Spine pain is one of the most prevalent health conditions that generated longer time off work over the last decade. In 2017, there were 95,600 temporary absences due to disability to spinal pain and leading cause of early retirement in Brazil. Even though Brazil’s Social Security makes the data publicly available, the specific statistics on spinal sick leave are not consolidated in publications. Therefore, the chapter 2 will address data on leave from work by Social Security due to spinal pain, in order to describe the number of benefits granted for spinal pain between 2008 and 2017. In addition, this chapter will describe the demographic and clinical data from the studied population. For this, we performed an analysis of data from Brazil Social Security, in which the data of benefits granted for diagnosis of spine pain were selected according to the International Classification of Diseases (ICD-10) of the group of spinal pain (M40 to M54). The data were obtained through the Social Security Statistical Yearbook and the Unique Benefits System. The benefits were stratified in the descriptive analyzes according to the type of benefits (temporary and permanent), spinal pain site (cervical, thoracic and lumbar) and etiology (specific and non-specific). As a result, we found that spinal pain was responsible for 2,150,488 social security benefits, corresponding to 4.5% of all benefits granted between 2008 and 2017. Most of the benefits were granted to patients aged between 30 and 59 years (83.5%) and 88.3% were commercial workers. A higher prevalence in the granting of social security benefits for low back pain (43.9%) and pain in an unspecified region (46.4%) were identified. In addition, we found that most of the benefits granted were classified with non-specific diagnoses of the spine (58.1%) according to the ICD-10. Most of the benefits granted were temporary (93.6%) and lasted up to 3 months (59.5%). Thus, we can conclude that spinal pain is a frequent cause of temporary and permanent leave from work in Brazil. Most of the beneficiaries were both in the productive age range and they were commercial workers. There was a high prevalence of sick leave among beneficiaries with low back pain. Most of the benefits were temporary and have short duration. This study provides important data on sick leave from work in developing countries and demonstrates the need to make public policies to prevent and promote health, aiming to reduce sick leave from work and costs due spine pain. The high prevalence of low back pain, it is increasingly important to seek prevention and treatment measures for chronic low back pain. Clinical practice guidelines recommend non-pharmacological interventions and endorse the use of exercises to improve pain and function. Similarly, most guidelines do not recommend the use of passive therapies, such as electrophysical agents, as they are ineffective for low back pain. However, some guidelines consider these therapies as an additional option to active treatments. Among passive therapies, photobiomodulation therapy is recommended for the treatment of chronic low back pain by the American College of Physicians (ACP) guideline. In contrast, although the National Institute for Health and Care Excellence (NICE) guideline do not recommend the use of photobiomodulation therapy due to conflicting evidence, these guidelines state that evidence of the clinical benefits of PBMT cannot be ruled out. Thus, it is observed that the current evidence of the effects of photobiomodulation therapy on low back pain is still conflicting. Therefore, in chapters 3 and 4 we discuss the effects of photobiomodulation therapy against placebo on pain intensity, general and specific disability, and the global perceived effect in patients with chronic nonspecific low back pain in the short, medium and long term. For this, we conducted a randomized, placebo-controlled study, blinding patients, therapists and evaluators. The study was carried out at the Center of Excellence in Clinical Research in Physiotherapy at Universidade Cidade de São Paulo, between April 2017 and May 2019. A total of 148 patients with chronic low back pain were randomized to either active photobiomodulation therapy (n=74) or placebo (n=74). Patients from both groups received 12 treatment sessions, 3 times a week, for 4 weeks. Patients from both groups also received an educational booklet based on ‘The Back Book’. Clinical outcomes were measured at baseline and at follow-up appointments at 4 weeks, 3, 6 and 12 months after randomization. The primary outcomes were pain intensity and disability measured at 4 weeks. We estimated the treatment effects using linear mixed models following the principles of intention to treat. The results showed that there were no clinical important between-group differences in terms of pain intensity (Mean Difference=0.01 point; 95% CI=-0.94 to 0.96) and disability (Mean Difference=-0.63 points; 95% CI=-2.23 to 0.97) at 4 weeks. Photobiomodulation therapy was not better than placebo in patients with chronic nonspecific low back pain.